Audit activity and quality of completed audit projects in primary care in Staffordshire. Issue 3 (September 1995) - Chambers, R; Bowyer, S; Campbell, I
Abstract : OBJECTIVES–To survey audit activity in primary care and determine which practice factors are associated with completed audit; to survey the quality of completed audit projects. DESIGN–From April 1992 to June 1993 a team from the medical audit advisory group visited all general practices; a research assistant visited each practice to study the best audit project. Data were collected in structured interviews. SETTING–Staffordshire, United Kingdom. SUBJECTS–All 189 general practices. MAIN MEASURES–Audit activity using Oxford classification system. Quality of best audit project by assessing choice of topic; participation of practice staff; setting of standards; methods of data collection and presentation of results; whether a plan to make changes resulted from the audit; and whether changes led to the set standards being achieved. RESULTS–Audit information was available from 169 practices (89%). 44(26%) practices had carried out at least one full audit; 40(24%) had not started audit. Mean scores with the Oxford classification system were significantly higher with the presence of a practice manager (2.7(95% confidence interval 2.4 to 2.9) v 1.2(0.7 to 1.8), p < 0.0001) and with computerisation (2.8(2.5 to 3.1) v 1.4 (0.9 to 2.0), p < 0.0001), organised notes (2.6(2.1 to 3.0) v 1.7(7.2 to 2.2), p = 0.03), being a training practice (3.5(3.2 to 3.8) v 2.1(1.8 to 2.4), p < 0.0001), and being a partnership (2.8(2.6 to 3.0) v 1.5(1.1 to 2.0), p < 0.0001). Standards had been set in 62 of the 71 projects reviewed. Data were collected prospectively in 36 projects and retrospectively in 35. 16 projects entailed taking samples from a study population and 55 from the whole population. 50 projects had a written summary. Performance was less than the standards set or expected in 56 projects. 62 practices made changes as a result of the audit. 35 of the 53 that had reviewed the changes found that the original standards had been reached. CONCLUSIONS–Evaluation of audit in primary care should include evaluation of the methods used, whether deficiencies were identified, and whether changes were implemented to resolve any problems found.